Apical Root Resorption after Orthodontic Treatment - P. Černochová; L. Izakovičová Hollá (Czech Dental Chamber, 2012)
Aim: The aim of the present study was to assess the incidence of apical root resorption in patients treated with fixed orthodontic appliances and find out whether the frequency of their occurrence depends on sex, patient's age, Angle class malocclusion, total length and type of orthodontic treatment. Material and methods: The retrospective study comprised 150 randomly selected patients (75 males and 75 females) who had completed treatment with fixed orthodontic appliances. The measurements were performed on panoramic radiographs and lateral cephalograms taken before and after treatment with the fixed orthodontic appliance. Classification after Linge and Linge was used for the assessment of the apical root resorption. Results: No signs of apical root resorption were recorded in 32% patients and the irregular root contour in 38.7% patients. The apical root resorption exceeding one-third of the original root length was registered in 2 (1.3%) patients (1 female and 1 male). No significant differences in the incidence of apical root resorption were found in the sex, Angle class malocclusion and patient's age. The incidence of apical root resorption was significantly higher in patients with extractions (p = 0.012). The root resorption was significantly less frequent in patients with total length of treatment shorter than 22 months (p = 0.028). Significant differences were observed between the groups of patients with length of treatment shorter than 22 months and longer than 34 months (p = 0.003). Conclusions: The signs of apical root resorption of upper permanent incisors were observed in 68 % patients after fixed orthodontic treatment. It is possible consider the extraction orthodontic treatment and longer length of treatment as risk factors for apical root resorption.